RUHANA KUDDUS PELOPOR GERAKAN ENTERPRENEUR PEREMPUAN DI MINANGKABAU - Silfia Hanani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Ruhana Kudus is one of the developer of women’s economic movement in Minangkabau in colonial era. One of the movement is establish an economic organization which can motivate the women to have entrepreneur spirit. The economic organization that established by Ruhana Kuddus is Amai Setia handicraft. In this organization, the women get guidance to make many handicrafts that earn and run the economy, then those handicrafts will be sold in the market. The profit of the handcraft selling will be used as women prosperity strengthening and also as one of the helper in running life at economic section. The Economic activities that established by Ruhana Kuddus is in handcraft skill, so it mastered by the women, then it becomes one of house hold trading that still exist till now.